The Effect of Application of Work Safety and Health Management System (K3) and Organizational Culture On Employee Work Satisfaction In dr. Soepraoen Malang Hospital - Suripto, Suripto; Melda Suhita, Byba; Indasah, Indasah (Journal for Research in Public Health, 2019)
Occupational safety and health (K3) is an effort to create a safe and comfortable atmosphere to achieve the highest productivity. Factors which influence to achieve the purpose of these efforts, including the company's commitment; leadership policy regarding (K3); policies for the creation of a work environment in order to create K3, delegation of authority, implementation of training and education during the project; prevention of workplace accidents; tracing the main causes of work accidents; measure program performance (K3); and continuous documentation and records of work accidents. The research design used is quantitative research. The sampling technique used proportional sampling with a sample of 100 respondents. Data analysis techniques using multiple linear regression tests. The results show that there was a significant effect and the t test showed 6,665> t table (2,000), meaning that occupational safety and health had a significant effect on job satisfaction and there was a significant effect and the t test showed 6.802> t table (2,000), meaning spatial planning significant effect on employee job satisfaction. Based on the explanation, it can be concluded that the better the K3 management system, organizational culture, K3 management system, the higher the level of Employee Job Satisfaction at the Hospital. II dr. Soepraoen; and the organizational culture (X2) has the highest dominant influence toward employee satisfaction.